2015
DOI: 10.18869/acadpub.pbr.1.3.20
|View full text |Cite
|
Sign up to set email alerts
|

Hydroalcoholic and polyphenolic extracts of Ziziphus Jujuba Mill fruits prevent methyl methanesulfonate-induced DNA damage in HepG2 cells

Abstract: Introduction Constantly, cells undergo destructive oxidative stress processes, which could originate either from exogenous or endogenous sources. Cells withstand this occurrence through engaging several distinct defense mechanisms ranging from free radical scavengers such as glutathione (GSH), vitamins C, and antioxidant enzymes to the elaborate DNA repair systems (1). Genetic alterations to the DNA both in somatic and germ cells can induce a plethora of events, from single-point mutations to chromosomal break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Similar results were previously obtained for whole-fruit extracts of Z. mistol [ 32 ]. Although there are no reports on the genotoxicity of Z. mistol seed, pulp, and skin extracts, studies indicate the absence of toxicity for Z. jujuba extracts on the DNA of cells such as lymphocytes, PC12 cells, and HepG2 cells [ 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were previously obtained for whole-fruit extracts of Z. mistol [ 32 ]. Although there are no reports on the genotoxicity of Z. mistol seed, pulp, and skin extracts, studies indicate the absence of toxicity for Z. jujuba extracts on the DNA of cells such as lymphocytes, PC12 cells, and HepG2 cells [ 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained by us are in agreement with those reported by others. Ziziphus fruit extract was reported to be non toxic to PC12 cells [43], HepG2 cells [44] and normal human lymphocytes [45]. On the contrary cytotoxic activity of Ziziphus fruit extract was reported on tumor cells [45], breast cancer cells [46] and Triticum vegetal cells [47].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Etebari et al. [44] reported that Ziziphus jujuba could prevent genotoxicity induced by MMS in HepG2 cells. This reduction of DNA damage was attributed to the interactions of the phenolics, flavonoid, BA and the antioxidants present in Ziziphus .…”
Section: Discussionmentioning
confidence: 99%
“…The alkaline comet assay, a sensitive, cost-effective, and rapid technique for detecting DNA fragmentation in individual cells (21), was employed to determine the mode of cell death (apoptosis or necrosis) induced by the crude extract (20) from the Adenium obesum plant. The assay was performed as follows: 12×10 4 cells were seeded in a 24-well plate with 300 microliters of serum-free medium and incubated overnight for cell attachment.…”
Section: Alkaline Comet Assaymentioning
confidence: 99%